Determination of crop and soil evaporation coefficients for estimating evapotranspiration in a paddy field - Haofang, Yan; Chuan, Zhang; Oue, Hiroki; Guangjie, Peng; Darko, Ransford Opoku (International Journal of Agricultural and Biological Engineering, 2017)
Accurate estimation of evapotranspiration is important in efficient water management for improving water use efficiency. In order to obtain evapotranspiration and evaporation beneath the canopy using the Food and Agriculture Organization (FAO) method, pan evaporation was used instead of reference evapotranspiration calculated by the Penman-Monteith equation with detailed meteorological data. The total crop coefficient and soil evaporation coefficient were determined using actual measured daytime evapotranspiration and evaporation by the Bowen ratio energy balance and lysimeter, respectively, in a rice paddy field in Japan. The average evapotranspiration was 5.3 mm/d, 4.4 mm/d, 7.4 mm/d and 6.3 mm/d and crop coefficient was 0.79, 1.18, 1.01 and 0.86 for the initial stage, development stage, middle-season stage and late-season stage, respectively. The evaporation was low and almost constant with an average value around 0.77 mm/d when the leaf area index (LAI) reached 3. The proposed average crop coefficients for different growing stages were applied to estimate daytime evapotranspiration and found suitable. A simple soil water evaporation coefficient model was developed using leaf area index for practical use and it was found that it could accurately estimate evaporation. Keywords: evapotranspiration, evaporation, paddy field, lysimeter, leaf area index (LAI), Bowen ratio energy balance DOI: 10.25165/j.ijabe.20171004.2290 Citation: Yan H F, Zhang C, Oue H, Peng G J, Darko R O. Determination of crop and soil evaporation coefficients for estimating evapotranspiration in a paddy field. Int J Agric & Biol Eng, 2017; 10(4): 130–139.